Introduction to the theory and practice of econometrics - Judge, George G. (New York : Wiley, 1988)
This second edition of the introduction to econometrics retains its comprehensive nature and while incorporating much new material. New to this edition are a complete treatment of Bayesian inference, sampling theory, an appendix on linear algebra, and a computer handbook. Presentation covers modern statistical models and focuses on the sampling theory process by which the data were generated, and the statistical consequences of alternative decisions under uncertainty. Asymptotics are introduced early on, for use throughout. At least one applied example is included to illustrate each model and there are also many analytical and numerical exercises.
Includes bibliographical references and index.
rpm 28/06/2017
Loans
Keywords: Econometrics